2017
DOI: 10.3847/1538-4357/aa93e2
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Motion of Solar Magnetic Bright Points at High Resolution

Abstract: Magnetic bright points in the solar photosphere, visible in both continuum and G-band images, indicate footpoints of kilogauss magnetic flux tubes extending to the corona. The power spectrum of bright-point motion is thus also the power spectrum of Alfvén wave excitation, transporting energy up flux tubes into the corona. This spectrum is a key input in coronal and heliospheric models. We produce a power spectrum of bright-point motion using radiative magnetohydrodynamic simulations, exploiting spatial resolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…These two populations are divided in size: the large granules have diameters in a Gaussian distribution of approximately 1.2 ± 0.5 Mm and are believed to be traditional convective cells, whereas the smaller granules (or granule-like visible features) follow a decreasing power-law distribution in diameter, with typical sizes under 0.5 Mm. This population of smaller features may have its origin in turbulent processes at the solar surface rather than convection (Van Kooten & Cranmer 2017), meaning they may follow different distributions in timescale τ c and temperature contrast Θ RMS than those assumed in the present work's model. Abramenko et al (2012) quantify the importance of a given size of granule to the overall appearance of the photosphere with the area contribution function (ACF), defined as the ratio of the total area of granules of a given size to the total area available, and this should serve as a good proxy of the influence of granules (or granule-like features) of a given size on F 8 .…”
Section: Granular Sizementioning
confidence: 58%
“…These two populations are divided in size: the large granules have diameters in a Gaussian distribution of approximately 1.2 ± 0.5 Mm and are believed to be traditional convective cells, whereas the smaller granules (or granule-like visible features) follow a decreasing power-law distribution in diameter, with typical sizes under 0.5 Mm. This population of smaller features may have its origin in turbulent processes at the solar surface rather than convection (Van Kooten & Cranmer 2017), meaning they may follow different distributions in timescale τ c and temperature contrast Θ RMS than those assumed in the present work's model. Abramenko et al (2012) quantify the importance of a given size of granule to the overall appearance of the photosphere with the area contribution function (ACF), defined as the ratio of the total area of granules of a given size to the total area available, and this should serve as a good proxy of the influence of granules (or granule-like features) of a given size on F 8 .…”
Section: Granular Sizementioning
confidence: 58%
“…The choice of a Kolmogorov spectrum at high frequencies is motivated by the observational indications that photospheric motions are turbulent. Regarding the form of the spectrum at low frequencies, recent computations by Van Kooten & Cranmer (2017) suggest a rather flat spectrum for low frequencies, i.e., L ≈ 0, while Tu & Song (2013) and Arber et al (2016) propose a low-frequency exponent of L = 5/6. These two possible choices for L are considered to determine if this dependence has any impact on the results.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…They suggested that the mini-granules behave in a turbulent manner compared with their regular-size counterparts. van Kooten & Cranmer (2017) analyzed the motions of bright points in a numerically simulated photosphere and concluded that mini-granules cause high-frequency motions and regular-size granules cause low-frequency motions. They further suggested that there might be more power observed in small-scale and high-frequency phenomena.…”
Section: Introductionmentioning
confidence: 99%